Comprehensive transcriptomic analysis and meta-analysis identify therapeutic effects of N-acetylcysteine in nonalcoholic fatty liver disease - Yang, Keungmo; Kim, Hee-Hoon; Shim, Young-Ri; Ryu, Tom; Kim, Chang Wook (Frontiers in Pharmacology, 2023)
Introduction: The continuous rise in the prevalence of nonalcoholic fatty liver disease (NAFLD) is emerging as a global health issue. Although the protective effects of N-acetylcysteine (NAC), an antioxidant, against various diseases have been reported, it is still unclear whether NAC has therapeutic potential in NAFLD. Thus, the present meta-analysis aimed to investigate the efficacy of NAC on NAFLD in preclinical studies. Methods: By searching PubMed, Web of Science, and Cochrane Library, 13 studies were included. The methodological quality was assessed based on the SYstematic Review Centre for Laboratory animal Experimentation guideline, and heterogeneity was evaluated with I2 and p values. Publication bias was assessed by Egger’s test and sensitivity analysis was performed. Results: The results showed that NAC treatment significantly improved systemic and hepatic lipid metabolism (p < 0.01), inflammation-related liver injury (p < 0.01), glucose intolerance (p < 0.05), and hepatic steatosis (p < 0.01) by restoring hepatic glutathione (GSH) (p < 0.05) and GSH reductase (p < 0.05) levels compared to controls in NAFLD-induced animals. Consistently, in bulk, single-cell, and spatial transcriptomics data, the abovementioned target pathways of NAC were strongly associated with NAFLD development in mice and patients. Conclusion: Our study suggests that NAC has therapeutic potential for NAFLD and should be considered for future clinical trials.